84.9k views
0 votes
PLEASE HELP Match each function formula with the corresponding transformation of the parent function y = - (x + 2)2. 1. y = - (x + 4)2 Reflected across the x-axis and the y-axis 2. y = - (x + 2)2 - 2 Translated right by 2 units 3. y = (x - 2)2 Translated left by 2 units 4. y = 2 - (x + 2)2 Translated down by 2 units 5. y = -x2 Translated up by 2 units 6. y = (x + 2)2 Reflected across the x-axis

User Drchuck
by
5.5k points

1 Answer

1 vote

So we are given the following function:
y=-(x + 2)^(2).

Before we can solve this problem, we need to know the following:

  • Given g (x) = f (x) + k; The graph of g(x) equals f(x) shifted k units vertically. If k > 0, the base graph shifts k units upward, and if k < 0, the base graph shifts k units downward.

  • Given g(x) = f (x - k); The graph of g(x) equals f(x) shifted k units horizontally. If k > 0, the base graph shifts k units to the right, and if k < 0, the base graph shifts k units to the left.

  • The reflection of the point (x,y) across the x-axis is the point (x,-y).

  • The reflection of the point (x,y) across the y-axis is the point (-x,y).

Know we can solve the problem!

1.
y=-(x + 4)^(2). Translated left by 2 units.

2.
y=-(x + 2)^(2) - 2 Translated down by 2 units

3.
y=(x - 2)^(2) Reflected across the x-axis and the y-axis

4.
y= 2-(x + 2)^(2) Translated up by 2 units

5.
y=-(x)^(2) Translated right by 2 units

6.
y=(x + 2)^(2) y = (x + 2)2 Reflected across the x-axis

User Drprofee
by
4.8k points